Low grade glioma patients: how does this patient group perceive their quality of life prior to surgical or oncological interventions?. (12th October 2019) - Robinson, Charlotte; Pedro Lavrador, Jose; Gullan, Richard; Brazil, Lucy; Swampillai, Angela; Al'Salihi, Omar; Bhangoo, Ranj; Vergani, Francesco; Hurwitz, Vicky; La, Jess; Mullens, Laura; Ford, Liz; et al.
Abstract: Introduction: Literature analysing how patients with a provisional low-grade glioma perceive their own quality of life prior to any surgical or oncological intervention is scarce. This patient group are often highly functioning individuals, able to lead ordinary lives which stresses that their management must be carefully considered in a holistic sense. Low grade gliomas represent 5 % of brain tumours and they are typically of a younger cohort who will be less equipped to manage the uncertainties a diagnosis like this brings. Methods: Prospective single centre cohort study over 14 months where 56 patients completed the EORTC QLQ – BN 20 and 30 prior to initial consultation in the dedicated low grade glioma clinic. Results: 54% of patients did not feel 'limited in doing work or other daily activities' but of those who were affected to some degree, 21% of women felt 'very much affected' compared to 3% of men. 78% of patients expressed to a degree some 'uncertainty about the future' and this was shown to be a common theme among all age groups which reflects the huge burden of anxiety this patient group faces regardless of age. Conclusion: Data demonstrated a variety of quality of life scores that are not particular to a certain age group/gender which reinforces the importance of individual assessment as assumptions of patients in a particular category cannot be made. By assessing quality of life, clinical management is improved as a more in-depth assessment is facilitated on an individual basis and patient experience is enhanced.